IMPLIKASI PENERAPAN KEBIJAKAN GOLDEN VISA DALAM RANGKA MENDORONG PENGEMBANGAN INVESTASI PADA SEKTOR PARIWISATA - Angga Wijaya Holman Fasa; Mahardhika Berliandaldo; Dini Andriani; Ari Prasetio (JURNAL KEPARIWISATAAN, 2023)
Many countries already have efforts to accelerate tourism recovery (including the Government of Indonesia). One of the issued policies is facilitating investment in the tourism sector, which is expected to encourage economic growth and create sustainable jobs. This study uses a qualitative desk study approach or literature research to analyze the implications of implementing the golden visa policy to encourage investment development in the tourism sector. Besides, this study elaborates explicitly 3 (three) things: existing policies related to visa applications and the context of tourism investment, benchmarking of golden visa policies in some countries, and strategic policy implications.Â  Based on the analysis, a comprehensive approach is needed in formulating appropriate and relevant policies to support sustainable tourism investment, manifested in regulations along with adequate and effective implementation supervision. Related to the efforts to attract foreign investors to invest in Indonesia, and referring to the example of the application of the Golden Visa that has been carried out by several countries, existing policies in Indonesia can be added with several requirements in the prerequisite of golden visas aimed, so the goal of national economic development to prevent harmful excesses can be reached.